CAUSES OF DELAYED PRESENTATION OF ACUTE APPENDICITIS AND ITS IMPACT ON MORBIDITY AND MORTALITY - Asad, Shawana; Ahmed, Ashfaq; Ahmad, Sajjad; Ahmed, Sohail; Ghaffar, Salma; Khattak, Irfan Ud Din (Journal of Ayub Medical College Abbottabad, 2015)
Background: Acute appendicitis is one of the commonest abdominal emergencies and appendectomy is one of the commonest emergency procedures performed all over the world. The study was done with an objective to evaluate the different causative factors for delayed presentation of appendicitis. Methods: This cross-sectional study was carried out in the Surgical C unit, at Ayub Teaching Hospital, Abbottabad, Pakistan from 20th June 2013 to 19th June 2014. A total of 130 patients presented with appendicitis in OPDs or emergency department. Detailed history, general physical and systemic examination especially abdominal examination was done along with investigations. Results: It was found that 23.08% of complicated appendicitis presentation is due to missed diagnosis by physicians, 30.77% is due to missed diagnosis by non-doctors, 23.08% is due to conservative management at DHQ hospitals by surgeons, and 23.08% presented late because of self-medication at home. Conclusion: All patients with pain Right iliac fossa, there should be suspected of appendicitis. Proper workup should be done to exclude it. If kept on conservative management then regular monitoring of vitals with laboratory investigations should be done.